The Analysis of Science Process Skills on Pre-Service Elementary School Teachers - Rif'at Shafwatul Anam (Al Ibtida: Jurnal Pendidikan Guru MI, 2020)
AbstractThis research aimed to figure out how Science Process Skills (SPS) of pre-service elementary school teachers from elementary to high schools are and to analyze the need to develop these skills in the lecturing program. The method of this research was quantitative research with survey design. The participants in this study were 85 pre-service teachers of early semester students of Elementary School Teacher Education Program. 31 pre-service teachers have science education backgrounds, while 54 pre-service teachers do not have them. The research data were obtained from the test instruments given to the participants, and the responses were later analyzed and classified. Research result shows that the SPS of pre-service teachers are inadequate on the indicators tested including: planning experiments, hypothesizing, communicating, and concluding. There is no difference between participants who are from the science background and those who are not. Hence, pre-service teachers need to start developing and improving their SPS in the lecture process in order for them to provide the most optimal science teaching.Keywords: science process skills, pre-service elementary pre-service teachers, science lesson. AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana Keterampilan Proses Sains (KPS) dari calon guru sekolah dasar mulai dari sekolah dasar sampai dengan sekolah menengah dan menganalisis kebutuhan untuk mengembangkan keterampilan ini dalam program perkuliahan. Penelitian ini menggunakan metode kuantitatif dengan desain survei. Partisipan dalam penelitian ini berjumlah 85 orang calon guru pada Program Pendidikan Guru Sekolah Dasar pada semester awal. 31 calon guru memiliki latar belakang sains dan 54 calon guru bukan berlatar belakang sains. Data penelitian didapatkan dari instrumen tes yang diberikan pada partisipan kemudian jawabannya dianalisis dan diklasifikasikan. Hasil penelitian menunjukkan bahwa KPS calon guru tidak memadai pada indikator yang diujikan yaitu: merencanakan percobaan, berhipotesis, berkomunikasi, dan menyimpulkan. Tidak ada perbedaan antara partisipan yang berasal dari latar belakang sains atau tidak. Oleh karena itu, calon guru perlu mulai mengembangkan dan meningkatkan KPS mereka dalam proses perkuliahan untuk memberikan pengajaran sains yang paling optimal.Kata kunci: keterampilan proses sains, calon guru SD, pembelajaran sains